Studies in the Ericoideae (Ericaceae). XII. The placing of the genus Blaeria into synonymy under Erica’, nomenclatural and taxonomic changes for the southern African region - E. G. H. Oliver (Bothalia: African Biodiversity & Conservation, 1993)
The reduction of the genus Blaeria to synonymy under Erica requires the publication of six new combinations and three new names for the nine taxa occurring in southern Africa. Four species are reduced to synonymy. Diagnostic features and distribution maps are provided.